TOWARDS A SPATIAL DECISION SUPPORT SYSTEM FOR TERRITORY PLANNING - Labed, Kaouter; Hamdadou , Djamila; Trifa , Mohamed (The journal of contemporary issues in business and government, 2024)
In this paper, we introduce a multicriteria flexible decision-making system for regional planning. The proposed spatial decision support system integrates several variants which contribute simultaneously to obtain a better territorial context analysis. The suggested Multicriteria Spatial Decision Support System (MC-SDSS) mainly employs an improved version of Electre III as a methodological evaluation approach. Indeed, the classical Electre III method suffers from a few irregularities that can be considerably minimized by the use of optimization methods issued from Artificial Intelligence and Operational Research. The proposed approach has improved the decision quality for territory decision makers in the realisation of regional planning projects and particularly in identifying a surface area that more effectively meets certain criteria.